A Novel Bifunctional Endolytic Alginate Lyase with Variable Alginate-Degrading Modes and Versatile Monosaccharide-Producing Properties - Peng, Chune; Wang, Qingbin; Lu, Danrong; Han, Wenjun; Li, Fuchuan (Frontiers in Microbiology, 2018)
Endo-type alginate lyases usually degrade alginate completely into various size-defined unsaturated oligosaccharide products (≥disaccharides), while exo-enzymes primarily produce monosaccharide products including saturated mannuronate (M) and guluronate (G) units and particularly unsaturated Δ units. Recently, two bifunctional alginate lyases have been identified as endolytic but M- and G-producing with variable action modes. However, endolytic Δ-producing alginate lyases remain undiscovered. Herein, a new Flammeovirga protein, Aly2, was classified into the polysaccharide lyase 7 superfamily. The recombinant enzyme and its truncated protein showed similar stable biochemical characteristics. Using different sugar chains as testing substrates, we demonstrated that the two enzymes are bifunctional while G-preferring, endolytic whereas monosaccharide-producing. Furthermore, the catalytic module of Aly2 can vary the action modes depending on the terminus type, molecular size, and M/G content of the substrate, thereby yielding different levels of M, G, and Δ units. Notably, the enzymes preferentially produce Δ units when digesting small size-defined oligosaccharide substrates, particularly the smallest substrate (unsaturated tetrasaccharide fractions). Deletion of the non-catalytic region of Aly2 caused weak changes in the action modes and biochemical characteristics. This study provided extended insights into alginate lyase groups with variable action modes for accurate enzyme use.